Smartphone Usage : Associations with Cognition, Motivation, and Sleep Patterns - Hite, Emily M.; Moeller, Madison D; Westerland, Sarah M.; Dortch, Sierra D.; Becker, Samuel J.; Langley, Camryn D.; Lehto, Elisabeth A.; Lortie, Margot M.; Leland, David S. (My University, 2019)
College students’ smartphone use presents concerns with academic dishonesty, distraction, sleep disturbances, and social withdrawal. We conducted a survey to focus on the relationship between phone use/attitudes and attention. We assessed how much students use their phone, how reliant they are on their phone, and their concerns about not having access to their phone. Regarding attention, we asked them about their difficulties with attention and focusing on the present moment, i.e. mindfulness. We also assessed their motivation to seek mental stimulation, i.e. sensation seeking. We predicted positive relationships between smartphone use/problems and both sensation seeking and ADHD-related difficulties. We also predicted negative associations between smartphone use/problems and both mindfulness and sleep amount/quality.
Color poster with text, charts, and graphs.
Keywords: Smartphones; College students; Behavioral assessment; Posters